Estabilización de fangos activos provenientes de planta de tratamiento de agua residual, mediante la técnica de bokashi - Sabando Vélez, Eliana Judyth (2022)
If not properly managed, the activated sludge produced by wastewater treatment plants is made up of high concentrations of pathogenic microorganisms and organic matter, among others, and if not properly managed, it becomes an environmental problem. The main objective of this study was to stabilize this sludge using the Bokashi technique, for which a completely randomized design (CRD) was carried out with four treatments and four replicates each. T1 contained 35 % sludge and 65 % Bokashi, T2 contained 45 % sludge and 55 % Bokashi, T3 contained 55 % sludge and 45 % Bokashi, and T4 contained 65 % sludge and 35 % Bokashi. According to the statistical analyses carried out in the IMB SPSS software, T3 achieved the best results for adequate sludge stabilization, presenting parameters of optimum moisture values of 46,35 %, carbon of 42,73 %, and nitrogen of 1,55%. Therefore, these values are considered ideal in relation to the carbon, the pH value of 6, 4 and the temperature that once stabilized was maintained between 30 and 31 ºC in comparison with the other treatments, accepting the hypothesis proposed.